English Teacher Identity in The Context of Zoning Policy Implementation - Hapsari, Anita Galuh Sri; Budiraharjo, Markus (Journal of Education Reseach and Evaluation, 2019)
Teacher identity still remains an important topic to discuss in education because it shows teachers’ personal and professional aspects. Teacher identity is not a static circumstance as it changes depending on the contexts. As zoning policy in new student admission in Indonesia remains as educational current issue, this study aims to explore how the zoning policy implementation develops English teacher identity in high and low-performing schools. This study employed qualitative approach as the purpose of this research is not to be generalized; this empirical research is aimed to reveal holistic discussion of particular subjects instead. Twelve English teachers from different public senior high schools in Yogyakarta Province, Indonesia were selected for semi-structured interviews and two of them were invited to have in-depth interviews. The data were coded and analyzed based on the framework of teacher identity construction. The results showed that the contribution of zoning policy implementation in teacher identity development varied. Firstly, zoning policy implementation influences teacher identity regarding their beliefs on students’ characteristics in high and low-performing schools. Secondly, teachers’ maintenance of their moral purpose as educator was developed through the implementation. Thirdly, class dynamics were triggered by the previous two aspects